Free DNA partially clarifies discrepancies between qPCR and the conventional phage quantification method. - Saar Van Overfelt; Hans Duyvejonck; Femke Baeke; Riet De Rycke; Maya Merabishvili; Stefan Vermeulen; Piet Cools; Mario Vaneechoutte; Els Van Mechelen (PLoS ONE, 2024)
To use phages in a personalized therapy and industrial applications, an accurate quantification is needed. The gold standard method, namely the culture-based double agar overlay (DAO) method, provides an accurate estimate of the number of infectious phages but is laborious and time-intensive. Quantitative polymerase chain reaction (qPCR) can be used as a fast alternative but tends to overestimate the number of infectious phage particles. Here we describe the use of a DNase treatment before quantification of the Staphylococcus aureus phage ISP with qPCR to obtain a more accurate estimate of the number of infectious phage particles. We showed that DNase treatment results in a significant decrease of the concentration when measured with qPCR although for two out of three tested ISP phage stocks, there was still a significant difference with the DAO method. We also showed that the discrepancy between quantification with qPCR and the DAO method is dependent on the storage period of the phage stock, with a larger discrepancy for older stocks. Additionally, we used negative contrast immune electron microscopy to confirm the presence of DNA in the medium of the phage stock and the impact of the DNase treatment on the free DNA.